2013
DOI: 10.1186/1472-6963-13-445
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated to referral of tuberculosis suspects by private practitioners to community health centres in Bali Province, Indonesia

Abstract: BackgroundThe contrast between the low proportion of tuberculosis (TB) suspects referred from private practitioners in Bali province and the high volume of TB suspects seeking care at private practices suggests problems with TB suspect referral from private practitioners to the public health sector. We aimed to identify key factors associated with the referral of TB suspects by private practitioners.MethodsWe conducted a case-control study conducted in Bali province, Indonesia. The cases were private practitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 5 publications
4
17
0
Order By: Relevance
“…But, studies have shown that PPs in India do not often adhere to these standards [ 34 ]. A study from Indonesia has demonstrated that exposure of PPs to the National TB program improves referral of TB cases to National TB program [ 35 ]. In our study, all the actively-referring PPs were familiar and trusted the functioning of the RNTCP.…”
Section: Discussionmentioning
confidence: 99%
“…But, studies have shown that PPs in India do not often adhere to these standards [ 34 ]. A study from Indonesia has demonstrated that exposure of PPs to the National TB program improves referral of TB cases to National TB program [ 35 ]. In our study, all the actively-referring PPs were familiar and trusted the functioning of the RNTCP.…”
Section: Discussionmentioning
confidence: 99%
“…The limited training on TB in the medical curriculum and limited opportunities for continuing medical education are likely contributing factors [ 7 ]. Finding appropriate ways to increase knowledge about TB therefore needs to be included in any project with PPs [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Engagement of PPs for TB care, while currently not undertaken, is among the NTP’s priority goals. Previous studies have recognized barriers to effective PP engagement including a lack of incentive, complicated TB reporting and referral systems, and lack of communication and trust between the private and public sectors [ 9 , 10 ]. Our feasibility study in allocated districts of Bandung City sought to investigate and understand the barriers to involving PPs in TB control, develop a system to reduce those barriers, and evaluate the feasibility of this system to increase the number of correctly diagnosed and notified new TB cases.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, community-based TB education is very important. It may be useful to educate and expose not only public, but also private practitioners to community-based TB programs [9,28].…”
Section: Discussionmentioning
confidence: 99%